Five-year survival after post-cardiotomy veno-arterial extracorporeal membrane oxygenation. Issue 6 (12th January 2021) - Biancari, Fausto; Perrotti, Andrea; Ruggieri, Vito G; Mariscalco, Giovanni; Dalén, Magnus; Dell'Aquila, Angelo M; Jónsson, Kristján; Ragnarsson, Sigurdur; Di Perna, Dario; Bounader, Karl; Gatti, Giuseppe; Juvonen, Tatu; et al.
Abstract: Aims : Veno-arterial (VA) extracorporeal membrane oxygenation (ECMO) support for post-cardiotomy cardiogenic shock (PCS) after adult cardiac surgery is associated with satisfactory hospital survival. However, data on long-term survival of these critically ill patients are scarce. Methods and results: Between January 2010 and March 2018, 665 consecutive patients received VA-ECMO for PCS at 17 cardiac surgery centres and herein we evaluated their 5-year survival. The mean follow-up of this cohort was 1.7 ± 2.7 years (for hospital survivors, 4.6 ± 2.5 years). In this cohort, 240 (36.1%) patients survived to hospital discharge. Five-year survival of all patients was 27.7%. The PC-ECMO score was predictive of 5-year survival in these patients (0 point, 50.9%; 1 point, 44.9%; 2 points, 40.0%; 3 points, 34.7%; 4 points, 21.0%; 5 points, 17.6%; ≥6 points, 10.7%; P < 0.0001). Age was among factors independently associated with late survival, patients >70 years old having a remarkably poor 5-year survival (<60 years: 39.2%; 60–69 years: 29.9%; 70–79 years: 12.3%; ≥80 years: 13.0%, P < 0.0001). Implantation of a ventricular assist device or heart transplant was performed in 3.2% of patients and their 5-year survival was 42.9% (for heart transplant, 63.6%). Conclusion : Veno-arterial extracorporeal membrane oxygenation for PCS is associated with satisfactory 5-year survival in young patients without critical pre-ECMO conditions. The use of VA-ECMO for PCS in patients >70 years should be considered only after a judicious scrutiny of patient's life expectancy. Future studies should evaluate whether satisfactory mid-term survival of these patients translates into a good functional outcome. Trial registration: Clinicaltrials.gov—NCT03508505.